2014
DOI: 10.1007/s12026-014-8599-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin replacement therapy in common variable immunodeficiency induces B cell depletion through differentiation into apoptosis-prone CD21low B cells

Abstract: Intravenous immunoglobulin (IVIG), besides its use as replacement therapy in patients with antibody deficiencies, is broadly used as an immunomodulatory agent for the treatment of autoimmune and inflammatory disorders. The mechanisms of action of IVIG include Fc receptor blockade, inhibition of cytokines and growth factors, modulation of macrophages and dendritic cells, enhancement of regulatory T cells, and modulation of B cells through the FcγRIIB receptor and CD22. Recent studies suggest that in vitro expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This effect is preceded by a profound modulation of B-cell homeostasis, where IVIG induces the down-regulation of CD21 expression promoting the generation of anergic-like, apoptosis prone CD21 low B-cells. We found that these newly generated CD21 low B-cells displayed the same peculiar pattern of receptors expressed by CD21 low B-cells present before IVIG, namely, increased FCRL4 and CD11c, and reduced CD62L expression ( 45 ).…”
Section: Ivig and B-cell Anergymentioning
confidence: 82%
See 1 more Smart Citation
“…This effect is preceded by a profound modulation of B-cell homeostasis, where IVIG induces the down-regulation of CD21 expression promoting the generation of anergic-like, apoptosis prone CD21 low B-cells. We found that these newly generated CD21 low B-cells displayed the same peculiar pattern of receptors expressed by CD21 low B-cells present before IVIG, namely, increased FCRL4 and CD11c, and reduced CD62L expression ( 45 ).…”
Section: Ivig and B-cell Anergymentioning
confidence: 82%
“…In addition, these newly generated CD21 low B-cells, upon overnight culture, undergo spontaneous apoptosis. These observations suggest that IVIG therapy in vivo , even at a replacement dosage, may influence antibody responses by inducing B-cell depletion through differentiation into CD21 low B-cells that undergo accelerated apoptosis ( 45 ).…”
Section: Ivig and B-cell Anergymentioning
confidence: 99%
“…The standard-of-care in CVID is life-long immunoglobulin replacement, which reduces the number of bacterial infections, alters cytokine production and B cell differentiation, and likely enhances survival [15][16][17][18]. IVIG is used for replacement therapy in CVID, but it also has immunomodulatory effects and is increasingly administered to treat autoimmune diseases, including immune thrombocytopenia, Kawasaki syndrome, immune hemolytic anemia, some neurological diseases, and graft versus host disease [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…CVID patients with expanded CD21low B cells have high constitutive ERK activation [BCR signaling pathway important for B cell anergy (41)], low responsiveness to TLR9 and BCR stimuli, defective calcium signaling (42, 43), and propensity to apoptosis. IVIg infusion administered in vivo transiently increased constitutive pERK, reduced the pERK increment induced by BCR cross-linking (44), and drove B cells to downregulate CD21 expression (45). …”
Section: B Cellsmentioning
confidence: 99%